(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Orally modified-release multiple-unit dosages have consistently shown themselves to be a more successful therapeutic choice than other dosage types. Novel medication delivery systems have several advantages over conventional multidose therapy. Current trends indicate that the use of micro particles in drug delivery systems can result in regulated or delayed release formulations for oral use with minimal risk of dose dumping, variable blending to achieve different release patterns, and predictable and short stomach residence time. In addition to their prolonged release, microspheres garnered significant interest for their capability to specifically target drugs. It has been demonstrated that oral modified-release multiple-unit dosage is a more efficacious treatment option in comparison to traditional or quick-release single-unit dosage forms. Innovative drug delivery methods are superior to traditional multidose therapy in a number of ways. According to current trends, the use of microparticles in drug delivery systems can lead to formulations that are regulated or released gradually for ingestion with a low risk of dose dumping, blending that can be adjusted to achieve diverse release patterns, and a stomach residence period that is predictable and brief. In addition to their extended release, microspheres attracted a lot of attention due to their capacity to target medications precisely.